2022
DOI: 10.1111/epi.17228
|View full text |Cite
|
Sign up to set email alerts
|

A pharmacogenomic assessment of psychiatric adverse drug reactions to levetiracetam

Abstract: Objective: Levetiracetam (LEV) is an effective antiseizure medicine, but 10%-20% of people treated with LEV report psychiatric side-effects, and up to 1% may have psychotic episodes. Pharmacogenomic predictors of these adverse drug reactions (ADRs) have yet to be identified. We sought to determine the contribution of both common and rare genetic variation to psychiatric and behavioral ADRs associated with LEV.Methods: This case-control study compared cases of LEV-associated behavioral disorder (n = 149) or psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…When considering the safety analysis, both ASMs were found to be well tolerated, with similar retention rates during the long-term follow-up in the entire cohort. A higher number of adverse effects was observed in the levetiracetam group, especially in terms of behavioral adverse effects and drowsiness, confirming previous literature findings . Accordingly, our data suggest that the use of lamotrigine may be preferable in absence epilepsy and GTCA in the presence of psychiatric comorbidities, based on the comparable effectiveness of lamotrigine and levetiracetam in these specific syndromes and their tolerability profile.…”
Section: Discussionsupporting
confidence: 67%
“…When considering the safety analysis, both ASMs were found to be well tolerated, with similar retention rates during the long-term follow-up in the entire cohort. A higher number of adverse effects was observed in the levetiracetam group, especially in terms of behavioral adverse effects and drowsiness, confirming previous literature findings . Accordingly, our data suggest that the use of lamotrigine may be preferable in absence epilepsy and GTCA in the presence of psychiatric comorbidities, based on the comparable effectiveness of lamotrigine and levetiracetam in these specific syndromes and their tolerability profile.…”
Section: Discussionsupporting
confidence: 67%
“…17 The study of Campbell et al indicated that 1% of people exposed to LEV develop ADRs hence, they utilized a variety of approaches to assess the role of genetic variation in psychiatric and behavioral ADRs associated with LEV. 18 In their casecontrol study, they compared cases of LEV-associated behavioral disorder or psychotic reaction to LEV-exposed people without history of psychiatric ADRs and they showed that polygenic burden for schizophrenia is a risk factor for LEV-induced psychotic reaction. Their recommendation included the possibility of screening individuals with epilepsy to identify those at risk of developing ADRs and clinical knowledge on clinical risk factor such as history of depression and use of recreational drug.…”
Section: Discussionmentioning
confidence: 99%
“…Their recommendation included the possibility of screening individuals with epilepsy to identify those at risk of developing ADRs and clinical knowledge on clinical risk factor such as history of depression and use of recreational drug. 18 Though was commonly associated with a history of psychiatric disorder, the study by Molokwu et al deduced that there can be de novo presentation of this drug reaction. 19 Some studies showed that the higher risk for developing psychiatric symptoms from LEV can be attributed to a genetic predisposition.…”
Section: Discussionmentioning
confidence: 99%
“…Frontiers in Genetics frontiersin.org pharmacogenomic study of psychiatric ADR and levetiracetam revealed no association in either common or rare genetic variants (Campbell et al, 2022). However, Campbel et al utilized a hypothesis-free analysis that included a greater number of genes, and no statistically significant results were found after correction for multiple comparisons.…”
Section: Figurementioning
confidence: 99%